Guru Profesional: Perspektif Al Qur’an dan UU No 14 Tahun 2005 dalam Meningkatkan Mutu Pendidikan di Era Revolusi Industri 5.0 - K, Khairunnisa; Vedira, Mila; C, Charles; Pratama, Andy Riski (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Professional teachers have a very significant role in producing the next generation who are not only intellectually intelligent but also have noble morals. In the era of the Industrial Revolution 5.0, teachers are not only required to be able to master technology, but also to be able to instill Islamic moral and ethical values in students so that they can develop critical and innovative thinking skills while still adhering to Islamic principles. This research discusses the concept of professional teachers from the perspective of the Al-Qur'an , as well as its relevance to Law no. 14 of 2005 Article 8 concerning teachers and lecturers, with the hope of being able to contribute and add new perspectives in order to increase teacher professionalism. This research uses a qualitative approach with the library research method, where primary data sources are the Al-Qur'an and hadith, while secondary data sources include related books and journals. The tahlili method is used to analyze and interpret the meaning contained in these two sources. The research results show that Al-Qur'an letter underlines the importance of effective communication and teaching based on human values, which is in line with the principles of teacher professionalism regulated in Law no. 14 of 2005. In addition, the role of teachers as educators is not only limited to transferring knowledge, but also includes developing the character and morals of students. The conclusion of this research confirms that the integration of Al-Qur'an values with legal provisions can provide a strong foundation for the development of teacher professionalism in Indonesia.